CARDIOVASCULAR HEALTH VULNERABILITY OF THE ELDERLY POPULATION OF SÃO PAULO, BRAZIL DUE TO AIR POLLUTION - Gomes, Ana Carla dos Santos; Spyrides, Maria Helena Constantino; Lúcio, Paulo Sérgio; Lara, Idemauro Antonio Rodrigues de (Revista Brasileira de Climatologia, 2021)
The objective of this work was to verify the association between air pollutants and deaths of elderly people from acute myocardial infarction in the city of São Paulo by relative risk modelling. Taking into account the specific characteristics of the data under study, generalized estimating equations are used. Thus, the estimated risk of deaths by AMI of the exposed population increased by 3% due to CO, 6% because of SO2, 4% due to O3 and 9% due to PM10. The results contribute to health planning and environmental policies.